ANALISIS KELINCAHAN DAN KELENTUKAN TERHADAP KEMAMPUAN MENGGIRING BOLA BASKET PADA SISWA SMP NEGERI 2 SUNGAI DURIAN KOTABARU - SITTI MAIFA; ARHAM SYAHBAN (STKIP Paris Barantai, 2017)
This study aims to determine the contribution agility and flexibility of the abilities dribble basketball in students of SMP Negeri 2 Sungai Durian Kotabaru. The research method used is descriptive method with data collection techniques using test and measurement techniques against agility and flexibility and the contribution of each variable to the ability to dribble basketball. The population of this research is students of SMP Negeri 2 Sungai Durian Kotabaru as many as 30 students. The Samples of students of SMP Negeri 2 Sungai Durian Kotabaru taken by saturation sampling so that the total sample amounted to 30 students. From the results of the research is known there is contribution agility (X1) to the ability to dribble basketball in the students of SMP Negeri 2 Sungai Durian Kotabaru (Y) of 31.3%. There is a contribution of flexibility (X2) to the ability to dribble basketball in the students of SMP Negeri 2 Sungai Durian Kotabaru (Y) of 27.3%. and there is a contribution of agility (X1) and flexibility (X2), together to the ability to dribble basketball in at students of SMP Negeri 2 Sungai Durian Kotabaru (Y) of 43.3%. Keywords: agility, flexibility, basketball dribbling ability